Sistersong - Holland, Lucy (Redhook, 2021)
"In the ancient kingdom of Dumnonia, there is old magic to be found in the whisper of the wind, the roots of the trees, the curl of the grass. King Cador knew this once, but now the land has turned from him, calling instead to his three children. Riva can cure others, but can't seem to heal her own deep scars. Keyne battles to be accepted for who he truly is--the king's son. And Sinne dreams of seeing the world, of finding adventure. All three fear a life of confinement within the walls of the hold, their people's last bastion of strength against the invading Saxons. However, change comes on the day ash falls from the sky. It brings with it Myrdhin, meddler and magician. And Tristan, a warrior whose secrets will tear them apart. Riva, Keyne and Sinne--three siblings entangled in a web of treachery and heartbreak, who must fight to forge their own paths. Their story will shape the destiny of Britain"--Dust jacket flap